Standing up from a chair as a dynamic equilibrium task: a comparison between young and elderly subjects - Mourey, F; Grishin, A; d'Athis, P; Pozzo, T; Stapley, P (The journals of gerontology. Series A, Biological sciences and medical sciences, 2000)
The purpose of this study was to analyze and compare the features of center of mass (CoM) control along anterior/posterior axis in young and elderly subjects during sit-to-stand (STS). From a sitting position, seven healthy young subjects and seven healthy elderly subjects were asked to stand up from a chair under different experimental conditions (visual conditions: normal and blindfolded; speed: normal and as fast as possible). Analysis of results was based upon the concept of a "dynamic equilibrium area" (DEA), which in turn identified the dynamic limits of balance. The results showed that both the maximal CoM velocity in the horizontal axis and the CoM velocity at the instant of seat-off were found to be lower in elderly compared with young subjects. Concerning the maximal CoM velocity, the difference was increased under blindfolded condition. The position of CoM in the phase plane (i.e., velocity according to displacement) at the instant of seat-off was found to be shifted backward in elderly subjects. From these results we can deduce that age-related modifications can he observed in the control of the horizontal CoM motion during STS in healthy elderly subjects.